Theoretical Insight Into the Ultralong Room-Temperature Phosphorescence of Nonplanar Aromatic Hydrocarbon - Qin, Ke; Gong, Wenqi; Gao, Jia; Hu, Deping; Shi, Huifang; Yao, Wei; An, Zhongfu; Ma, Huili (Frontiers in Chemistry, 2021)
Purely aromatic hydrocarbon materials with ultralong room-temperature phosphorescence (RTP) were reported recently, but which is universally recognized as unobservable. To reveal the inherent luminescent mechanism, two compounds, i.e., PT with a faint RTP and HD with strong RTP featured by nonplanar geometry, were chosen as a prototype to study their excited-state electronic structures by using quantum mechanics/molecular mechanics (QM/MM) model. It is demonstrated that the nonplanar ethylene brides can offer sigma-electron to strengthen spin-orbit coupling (SOC) between singlet and triplet excited states, which can not only promote intersystem crossing (ISC) of S1->Tn to increase the population of triplet excitons, but also accelerate the radiative decay rate of T1->S0, and thus improving RTP. Impressively, the nonradiative decay rate only has a small increase, owing to the synergistic effect between the increase of SOC and the reduction of reorganization energy of T1->S0 caused by the restricted torsional motions of aromatic rings. Therefore, a bright and long-lived RTP was obtained in aromatic hydrocarbon materials with twisted structure. This work provided a new insight into the ultralong RTP in pure organic materials.